Study of Effectiveness of Pattern Based Teaching Method on Students’ Long-Term Retention of Contents in Organic Chemistry - Chandra Prakash Pokharna; Neetu Bharatiyaa (International Journal of Chemistry Education Research, 2021)
Organic chemistry is a subject which students find difficult because of complex reactions and mechanisms involved. The main aim of this study was to study the students' understanding of the concepts of organic chemistry by pattern based teaching method (PBT). Pattern Based Teaching is a systematic approach in teaching chemistry where the reactions and mechanisms are systematized into a particular pattern for different functional groups. The students are made to understand the basic concepts how to introduce a particular functional group and how functional groups give reactions with different type of reagents. The present paper reports the effect of this innovative teaching method on students' long term retention of organic chemistry course material. Long term retention of contents was examined by conducting two tests-pretest (based on traditional lecture teaching) and a post-test (conducted after PBT). Students' of first year undergraduate class of two different colleges of Kishangarh city of Ajmer district of Rajasthan were used for the study. These students were divided into six groups and two of them were taught by the author by PBT method. The rest four groups were control groups taught by the traditional lecture based teaching method. Students performance after PBT method was compared to that in a traditional lecture based teaching method. Our analysis showed that the out of the six sample groups of students used in our study, the highest mean scores (10.46 and 13.36) were of the two experimental groups. The four control groups had mean scores in the range 7-10. This investigation thus suggests that pattern-based teaching in organic chemistry is a powerful and systematic approach which facilitates students’ long-term retention of contents of the subject. It promotes active learning and creates students’ interest in the subject.